Distribution and Habitat Preference of Sloth Bear in Chitwan National Park, Nepal - Ghimire, Dinesh; Thapa, Tej Bahadur (Journal of Natural History Museum, 2015)
Effective conservation of Sloth bear requires detailed information regarding their distribution and habitat use. This study attempted to generate baseline data on distribution and habitat preference of Sloth Bear in Chitwan National Park, Nepal during March–May 2012. The study area was divided into 74 grids each measuring 16 Km2. Of the total grids, 35 were randomly selected for occupancy sampling. A total of 288 spatial replicates were sampled in 35 different grids recording 87 direct or indirect evidences of Sloth bear. Among them, 50 diggings, 25 scats, four scrapes with live animals in eight points were detected in four different habitat types of the Park. The variance to mean ratio showed clumped distribution of Sloth bear. The RPI values revealed that the mixed forest was found to be most preferred (RPI = 0.42) by Sloth Bear followed by grassland (RPI = 0.21). Riverine forest and Sal forest were less preferred (RPI = -0.25 and -0.11 respectively) but not avoided. Distribution of Sloth bear was influenced by distance to nearest water sources, distance to road and altitude. Similarly, disturbances like human activities, presence of cattle and fi re were found to affect the distribution of Sloth bear.J. Nat. Hist. Mus. Vol. 28, 2014: 9-17